P496 Antenatal thiopurine exposure in women with IBD is associated with intrahepatic cholestasis of pregnancy. (30th January 2023) - Rosiou, K; Broglio, G; Lever, G; Chiu, C M; Stocker, L J; Chipeta, H; Glanville, T; Selinger, C P
Abstract: Background: Pregnant women with Inflammatory Bowel Disease (IBD) continue thiopurines to maintain remission. Intrahepatic cholestasis of pregnancy (ICP) is the most common liver disorder of pregnancy, often causing distressing maternal symptoms and with potential implications for pregnancy outcome. Case studies have reported treatment-resistant intrahepatic cholestasis of pregnancy in thiopurine-exposed IBD pregnancies. We aimed to investigate whether thiopurines are associated with an increased risk of ICP and the course of ICP in the setting of thiopurine therapy. Methods: Single-centre retrospective cohort study comparing incidence and course of ICP in thiopurine exposed vs non-exposed patients with IBD and compared with age-matched pregnant controls. Results: The IBD cohort consisted of 386 pregnancies in 243 patients with IBD, with 386 age-matched controls without IBD. In patients with IBD, ICP was more common amongst thiopurine exposed pregnancies (n=10 9.0% vs n=5 1.8%; OR 5.34 [1.78-16.02]; p=0.021). Only thiopurine exposure was associated with the development of ICP. Age, disease activity, IBD phenotype, previous surgery, mesalazine, biologic, and steroid exposure were not associated. All thiopurine exposed ICP cases (of which 4 received ursodeoxycholic acid) improved symptomatically without thiopurine discontinuation. The incidence of ICP was significantly lower in women without IBD compared with women with IBD (n=5 1.3% vs n=15 4.1%; p=0.039). Thiopurine-exposed IBD patients had higher odds of experiencing ICP compared to non-IBD controls (n= 10 9.0% vs n=5 1.3%; OR 7.55 [2.52-22.57]; p<0.001). IBD patients not exposed to thiopurines had a comparable ICP incidence to controls (n-=5 1.8% vs n=5 1.3%; p=0.75). Severe ICP (total serum bile acids ≥40 µmol/l) occurred in 80% of thiopurine exposed patients, vs 40% in non-exposed (p=0.25), vs 20% in controls (p=0.09). We found no evidence of an unfavourable course of ICP in thiopurine exposed IBD cases. Median week of delivery was not significantly different among ICP cases in all three groups (p=0.39). Conclusion: Thiopurine exposure was associated with a significantly increased risk of ICP amongst patients with IBD compared to non-exposed IBD patients and age-matched general population controls. The course of ICP was not significantly different in thiopurine exposed cases. Clinicians involved in the management of patients with IBD should be aware of the potential risk for ICP and assess bile acids when symptoms occur. Prospective studies are required to understand the potential relationship between thiopurine metabolites and ICP.